Decomposition of Turbulent Velocity Fields in an SI Engine - Erdil A.; Kodal A.; Aydin K. (Springer Science and Business Media LLC, 2002)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Turbulence; Turbulence filter; turbulence filter; turbulence; SI engines